2013
DOI: 10.1016/j.jacc.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The Burgeoning Epidemic of Morbid Obesity in Patients Undergoing Percutaneous Coronary Intervention

Abstract: Morbid obesity is increasing in prevalence among patients undergoing PCI and is associated with a higher risk of mortality and morbidity. These epidemiological changes have important implications for technical considerations of cardiac catheterization, design of the catheterization lab to accommodate these patients, and most importantly, for societal effort toward prevention of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…The majority of patients (84.3%) were either overweight or obese. Our study findings are comparable to other studies that have used PCI registries [ 10 , 11 , 30 ]. In the current study, we found that over time there was a significant trend of decreasing prevalence for the normal weight category of patients undergoing PCI ( p = 0.048).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The majority of patients (84.3%) were either overweight or obese. Our study findings are comparable to other studies that have used PCI registries [ 10 , 11 , 30 ]. In the current study, we found that over time there was a significant trend of decreasing prevalence for the normal weight category of patients undergoing PCI ( p = 0.048).…”
Section: Discussionsupporting
confidence: 91%
“…In other studies that have focused primarily on the comparison of normal weight and extremely obese (≥40 kg/m 2 ) patients undergoing PCI, researchers have reported that extremely obese patients have increased vascular complications [ 30 ] compared to normal weight individuals and higher rates of in-hospital mortality [ 29 31 ] compared to overweight individuals. In the current study, we were unable to examine the various classes of obesity due to the small numbers in each category.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that an increasing number of obese patients will require cardiac surgery. 4 While not always accurate, BMI is still a useful measure of overall body habitus since it is highly correlated with body surface area (BSA); 5 it is also commonly used in anthropometric measurements in most previous and new risk models for the Society of Thoracic Surgeons (STS). 5-7 …”
mentioning
confidence: 99%
“…We also showed a higher incidence of CI-AKI in obese patients, based on the reverse J-curve relationship between BMI and CI-AKI incidence. Buschur et al [ 39 ] found that poor fluoroscopic visualization and miscalculation of renal function is common in obese patients. We believe that a vulnerability to contrast media and an erroneous estimation of renal function are responsible for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%